Nationalsozialistisches Strafrecht Kontinuität und Radikalisierung - Ambos, Kai (Grundlagen des Strafrechts, 2019)
This innovative study regards National Socialist criminal law-in accordance with the theories of continuity and radicalisation-as the racist (anti-Semitic), nationalistic (Germanic) and totalitarian updating of the authoritarian and anti-liberal tendencies found in German criminal law at the turn of the 20th century and during the Weimar Republic. The author proves this thesis through systematic analysis of the works of relevant authors, focusing primarily on the texts, which speak for themselves, rather than on morally judging the people who wrote them. In doing so, he also examines the reception of German (National Socialist) criminal law in Latin America. The aforementioned continuity did not only exist from a past perspective (post-Weimar), but also from a forward-looking perspective ('the Bonn Republic' 1949-1990). In short, neither did National Socialist criminal law appear from nowhere, nor did it completely disappear after 1945, which has seamlessly led to the modern-day attempt to reconstruct the identity of this Germanic myth through the so-called 'neue Rechte' or 'New Right' political movement.